2005
DOI: 10.1111/j.1600-0722.2005.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological appearance and chemical composition of enamel in primary teeth from patients with 22q11 deletion syndrome

Abstract: Patients with 22q11 deletion syndrome have many and complex medical problems, including hypocalcemia and/or hypoparathyroidism. Odontological findings include enamel aberrations in both dentitions. In order to describe enamel morphology, chemical composition in primary teeth, and to investigate the relationship between medical history and morphological appearance, dental enamel was investigated in 38 exfoliated primary teeth from 15 children and adolescents. Morphology was studied by the use of a polarized lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Table 2 illustrates study characteristics for Ns-HypoPT studies (Humphreys, 1939; Hansted and Holst, 1952; Hinrichs, 1956; Thew and Goulston, 1962; Pisanty, 1966; Sjöberg, 1966; Greenberg et al, 1969; Hermans et al, 1969; Moshkowitz et al, 1969; Riley, 1969; Nally, 1970; Frensilli et al, 1971; Lovestedt, 1971; Assif, 1977; Pisanty and Garfunkel, 1977; Myllärniemi and Perheentupa, 1978; Lindeberg, 1979; Goepferd and Flaitz, 1981; Illum et al, 1981; Jensen et al, 1981; Nikiforuk and Fraser, 1981; Børglum Jensen et al, 1983; Harrell, 1983; Ingemarsson, 1984; Lyles et al, 1985; de Carvalho et al, 1986; Porter and Scully, 1986; Ahonen et al, 1990; Porter et al, 1992, 1995; Walls and Soames, 1993; Hershkovitz et al, 1995; Lukinmaa et al, 1996; Firth et al, 1997; Jaquez et al, 1997; Perniola et al, 1998; Fukui et al, 2000; Winer and Merke, 2000; Klingberg et al, 2002, 2005, 2007; Al-Malik, 2004; López-Jornet et al, 2005; Oberoi and Vargervik, 2005; Yang et al, 2005; da Silva Dalben et al, 2008; McGovern et al, 2008; Kelly et al, 2009; Pavlic and Waltimo-Siren, 2009; Toka et al, 2010; Wasersprung et al, 2010; Heliövaara et al, 2011; Kollios et al, 2011; Oberoi et al, 2011; Nordgarden et al, 2012; Ponranjini et al, 2012; El Batawi, 2013; Kamarthi et al, 2013; Nortjé, 2013; Ali et al, 2014; Srirangarajan et al, 2014; Laccetta et al, 2015; Matthews-Brzozowska et al, 2015; Bruserud et al, 2016; Ferre et al, 2016; Bjanid et al, 2017; Lewyllie et al, 2017; Mohsenipour et al, 2017) with subgroups A–E corresponding to the classifi...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 illustrates study characteristics for Ns-HypoPT studies (Humphreys, 1939; Hansted and Holst, 1952; Hinrichs, 1956; Thew and Goulston, 1962; Pisanty, 1966; Sjöberg, 1966; Greenberg et al, 1969; Hermans et al, 1969; Moshkowitz et al, 1969; Riley, 1969; Nally, 1970; Frensilli et al, 1971; Lovestedt, 1971; Assif, 1977; Pisanty and Garfunkel, 1977; Myllärniemi and Perheentupa, 1978; Lindeberg, 1979; Goepferd and Flaitz, 1981; Illum et al, 1981; Jensen et al, 1981; Nikiforuk and Fraser, 1981; Børglum Jensen et al, 1983; Harrell, 1983; Ingemarsson, 1984; Lyles et al, 1985; de Carvalho et al, 1986; Porter and Scully, 1986; Ahonen et al, 1990; Porter et al, 1992, 1995; Walls and Soames, 1993; Hershkovitz et al, 1995; Lukinmaa et al, 1996; Firth et al, 1997; Jaquez et al, 1997; Perniola et al, 1998; Fukui et al, 2000; Winer and Merke, 2000; Klingberg et al, 2002, 2005, 2007; Al-Malik, 2004; López-Jornet et al, 2005; Oberoi and Vargervik, 2005; Yang et al, 2005; da Silva Dalben et al, 2008; McGovern et al, 2008; Kelly et al, 2009; Pavlic and Waltimo-Siren, 2009; Toka et al, 2010; Wasersprung et al, 2010; Heliövaara et al, 2011; Kollios et al, 2011; Oberoi et al, 2011; Nordgarden et al, 2012; Ponranjini et al, 2012; El Batawi, 2013; Kamarthi et al, 2013; Nortjé, 2013; Ali et al, 2014; Srirangarajan et al, 2014; Laccetta et al, 2015; Matthews-Brzozowska et al, 2015; Bruserud et al, 2016; Ferre et al, 2016; Bjanid et al, 2017; Lewyllie et al, 2017; Mohsenipour et al, 2017) with subgroups A–E corresponding to the classifi...…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that enamel opacities and enamel hypoplasia develop in children who suffer from hypocalcemia during the period of enamel formation (secretion, mineralization, and maturation; Stimmler et al, 1973; Nikiforuk and Fraser, 1981; Fraser and Nikiforuk, 1982; Klingberg et al, 2005; Kelly et al, 2009). However, enamel opacities and hypoplasia are reported more often in the permanent than in the primary dentition (Nordgarden et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous clinical and histological studies have reported that high frequency of dental aberrations, foremost enamel hypoplasia and hypomineralisation, as well as high caries prevalence in patients with 22q11DS 11,12 . Apart from dietary and oral hygiene problems, impaired saliva secretion and altered composition regarding electrolytes and proteins are plausible explanations for the cariologic problems seen in many patients with 22q11DS 13 .…”
Section: Introductionmentioning
confidence: 97%